Natural products of traditional Chinese medicine treat atherosclerosis by regulating inflammatory and oxidative stress pathways - Meng, Tianwei; Li, Xinghua; Li, Chengjia; Liu, Jiawen; Chang, Hong; Jiang, Nan; Li, Jiarui; Zhou, Yabin; Liu, Zhiping (Frontiers in Pharmacology, 2022)
Atherosclerosis (AS) is a prevalent arteriosclerotic vascular disease that forms a pathological basis for coronary heart disease, stroke, and other diseases. Inflammatory and oxidative stress responses occur throughout the development of AS. Treatment for AS over the past few decades has focused on administering high-intensity statins to reduce blood lipid levels, but these inevitably damage liver and kidney function over the long term. Natural medicines are widely used to prevent and treat AS in China because of their wide range of beneficial effects, low toxicity, and minimal side effects. We searched for relevant literature over the past 5 years in databases such as PubMed using the keywords, “atherosclerosis,” “traditional Chinese medicine,” “natural medicines,” “inflammation,” and “oxidative stress.” We found that the PI3K/AKT, TLR4, JAK/STAT, Nrf2, MAPK, and NF-κB are the most relevant inflammatory and oxidative stress pathways in AS. This review summarizes studies of the natural alkaloid, flavonoid, polyphenol, saponin, and quinone pathways through which natural medicines used to treat AS. This study aimed to update and summarize progress in understanding how natural medicines treat AS via inflammatory and oxidative stress-related signaling pathways. We also planned to create an information base for the development of novel drugs for future AS treatment.